Une reconnaissance de la singularité en cancérologie - Thibaud Pombet (Anthropologie & Santé)
This article examines the practices of care personalization through the study of units dedicated to the care of teenagers and young adults with cancer in France (“TYA”, 15-25 years). For this purpose, field data were collected through participant observation over five months, carried out when I was an activity-coordinator in the first French unit dedicated to this population at the Saint-Louis Hospital. Mobilizing the recognition theory developed by Axel Honneth, the article shows how these medical and nursing practices reflect an attention given to the singularity, and generate specific moral expectations. Conflicts between caregivers and patients can therefore be interpreted as the result of disrespect, attesting to a gap between promises and recognition practices. Finally, the article analyzes the form of autonomy prescribed to young patients as part of this personalization of care.